REVOLUTIONISING THE SHARIAH SECRETARIAT FUNCTION THROUGH ARTIFICIAL INTELLIGENCE: PROSPECTS AND CHALLENGES FOR MALAYSIA’S ISLAMIC BANKING SECTOR - Bin Abdul Rahim, Mohamad Syafiqe (Journal of Central Banking Law and Institutions, 2025)
This paper examines the potential and challenges of integrating artificial intelligence (AI) as a transformative approach to revolutionising the Shariah Secretariat function in Malaysia’s Islamic banking sector. The Shariah Secretariat, as outlined by Bank Negara Malaysia’s Shariah Governance Policy Document, plays a vital role in facilitating and supporting the secretarial and administrative matters of the Shariah Committee. This study examines the potential of AI to significantly enhance the effectiveness of the Shariah Secretariat, particularly through process automation, document management, regulatory reporting, and decision-making processes. However, AI integration poses critical challenges regarding the clarity of accountability, liability, and ethical considerations due to the autonomous nature of AI-driven processes. The research underscores substantial gaps in Malaysia’s existing legal and regulatory frameworks governing the application of AI in Islamic banking. To address these challenges, the study suggests specific legislative changes and recommends that Malaysia’s National Guidelines on AI Governance and Ethics principles be made binding to ensure transparent, ethical, and accountable AI practices within Islamic banking. Drawing on international frameworks, including the European Union’s AI Act and the OECD AI Principles, this paper recommends a holistic approach to regulatory refinement in Malaysia, aiming to sustain technological innovation while safeguarding Shariah compliance, ethical standards, and public trust.